Association between physical fitness and quality of life with frailty in elderly - Salomé Rodríguez-Gutiérrez; Miguel Alarcón-Rivera; Yeny Concha-Cisternas; Pablo Valdés-Badilla; Eduardo Guzmán-Muñoz (Revista Cubana de Medicina Militar, 2022)
Introduction: Pathological aging causes anatomophysiological changes responsible for generating deterioration in the physical condition and quality of life of the elderly. Thus, an increase in the presence of geriatric syndromes such as physical frailty has also been observed. Objective: To determine if there is an association between physical condition and quality of life with the frailty in older adults. Methods: Correlational study. 84 people over 60 years of age (62 women and 22 men) were included. Physical fitness, quality of life and frailty were measured. Physical fitness was assessed with the Senior Fitness Test battery and quality of life was measured with the World Health Organization Quality of Life Old (WHOQOL-OLD) questionnaire. Frailty was determined with the Fried phenotype. Contingency tables were used to associate the study variables with frailty through the Chi-square test. Results: Frailty was associated with some components of physical fitness such as upper body strength (p= 0.038), lower body strength (p= 0.018), lower body flexibility (p= 0.004), aerobic endurance (p= 0.038), agility and dynamic balance (p= 0.002). Also, significant associations were observed with quality of life dimensions such as autonomy (p= 0.007), past, present and future activities (p= 0.018), social participation (p= 0.006) and intimacy (p= 0.038). Conclusion: There is an association between frailty with dimensions of quality of life and with variables of physical fitness.